A Dynamic Model of the Environmental Kuznets Curve : Turning Point and Public Poliy - Hannes Egli; Thomas M. Steger (ETH Zurich, CER-ETH - Center of Economic Research, 2005)
We set up a simple dynamic macroeconomic model with (i) polluting consump- tion and a preference for a clean environment, (ii) increasing returns in abate- ment giving rise to an EKC and (iii) sustained growth resulting from a linear final-output technology. The model captures two sorts of market failures caused by external effects associated with consumption and environmental effort. This model is employed to investigate the determinants of the turning point and the (relative) effectiveness of different public policy measures aimed at a reduction of the environmental burden. Moreover, the model offers a potential explana- tion of an N-shaped pollution-income relation. Finally, it is shown that the model is compatible with most empirical regularities on economic growth and the environment.
Keywords: Q5; O4; 330; Environmental Kuznets Curve; Pollution; Abatement; External Ef- fects; Economic Growth; Public Policy; Umweltbelastung; Wirtschaftswachstum; Umweltpolitik; Endogenes Wachstumsmodell; Environmental Kuznets Curve